(untitled) (Estudos Japoneses, 2002)
During the Meiji Period, there was an attempt of modernization in Japan by the introduction of techniques, philosophies and ideologies from the west. In the plan of literature, it also had the literary diversity by the introduction of literary movements such Romantism, Naturalism, Realism among others that had arrived almost concomitantly at Japan. The main Japanese literary groups that had adhered to the Romantism were three: the Bungakukai, the Myôjô and the Subaru. Shimazaki Tôson was the founder and idealizer of the First group and was distinguished for developing and producing Romantic innovative poems that follow a model called shintaishi (new poetical forms). In this work, our objective was to characterize the Japanese Romantism, establishing facts that show the influence of the western Romantism (France, England and Germany) about the called Romantic writer Shimazaki Tôson.